Republic of Moldova : Financial System Stability Assessment; Update. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper discusses key findings of the Financial System Stability Assessment (FSSA) on Moldova. The assessment reveals that vulnerabilities of the financial sector appear to be manageable. Stress tests on likely scenarios do not indicate major vulnerabilities for the banking system as a whole. Since the 2004 Financial Sector Assessment Program, the National Bank of Moldova (NBM) has made progress in identifying bank owners, an issue then flagged as a major vulnerability, but other financial supervisors have been considerably less successful in this respect.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet